Memories and Ancestrality in Dance Studios : Afro-Referenced Paths in Educator Training - Godoy, Kathya Maria Ayres de (2025)
This article elucidates the pedagogical trajectories explored during a session of the course "Dance Training Cycle - Dialogues between Dance and the São Paulo State Curriculum", designed to train Brazilian art educators employed within the São Paulo State Public Education Network. The event addressed both artistic and educational paths presented in the third meeting of the Cycle, entitled "Dances in Afro-Brazilian History and Culture", which proposed a work with the topics of dance language and creative processes as a teaching methodology that involves the appreciation of Afro-referenced dance knowledge with memory, through contact with Afro-Brazilian corporealities and oralities, referred to as Afro-referenced BodyOralities. This training provided a glimpse into the pedagogical dance proposal known as Dança Terreira. The outcomes of this process are disseminated through the production of four video documentaries included in this article. Furthermore, these educators are afforded the opportunity to develop further approaches to work with such content, thereby joining forces to build an education system that is more receptive to traditional ancestral wisdom.